VD_FINDINFO Pron / 2012 / 89 vom 27. April 2012 - VD Tribunal cantonal (2012)
FRAIS JUDICIAIRES, ASSISTANCE JUDICIAIRE, INDEMNITÉ ÉQUITABLE | 109 CPC (CH), 122 CPC (CH), 241 CPC (CH), 65 al. 2 TFJC (2010)